Teaching performance of the professors of pediatrics in postgraduate education in "Salvador Allende" Faculty. January-July 2016 - Martha Ortiz García; Lourdes de la Caridad Borges Oquendo; Guillermo Manuel Negrín Ortiz; Isis Rodríguez Ribalta; María Elena Sardiñas Arce; Rogelio Balado Sansón (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Teaching performance is the behavior of the professor during the teaching process with a conscious and individual character, which demonstrates the professional, personal, and social development of this specialist. The characterization of performance allows to identify the problems and potentialities in order to develop activities that favor their improvement. Objective: To characterize the teaching performance of the Professors of Pediatrics in Postgraduate Education in "Salvador Allende" Medical Faculty from January to July 2016. Material and methods: The research sample consisted of 21 of 32 professors, 2 directors, and 7 of 13 residents. Characterization of teaching performance started with the parametrization process. Teaching performance focused on competence was selected as the main variable. Five dimensions, 16 subdimensions, and 55 indicators were defined. Empirical inquiries consisted of interviews, surveys, performance observation, and document reviews. Descriptive statistics and the mode were used as the measures of central tendency.  Results: Methodological triangulation allowed to identify the following problems: insufficient planning of the autonomous work; deficient use of the information and communication technologies (ICTs) and foreign language; limited scientific production; insufficient professional and self-improvement in the specialty and in medical education. The following potentialities were identified: educational work carried out by the professors, proven dedication; and contribution to the formation of residents as citizens and professionals. Conclusions: The characterization of the teaching performance of the professors in postgraduate education allowed to identify problems in the following dimensions: methodological work, research and innovation work, and professional improvement. The teaching-learning process is being developed and the political-ideological work is considered a potentiality. Keywords: Teaching performance, Pediatrics Specialty, educational work, political-ideological work, methodological work, research and innovation work, personal improvement.